Garbage Management Using Internet of Things - SR, Reeja; Gaurav, Abhishek; Patel, Ladly; Cherian, Rino (International Journal of Computer Sciences and Engineering, 2025)
Increasing population and unhealthy lifestyle in urban and semi-urban areas is giving rise to catastrophic decline in cleanliness of surroundings. Recently there are several government programs and NGOS that are focused in making people aware in keeping their surroundings clean. This paper discusses about a system designed using Internet of Things (IoT) which informs organization as soon as garbage bin is full. Organization may include government body or any private firm that is responsible for garbage collection. Various sensors help detecting when the garbage bin is full and then via telegram it will inform the organizations to act. Gas sensor helps to detect toxic and harmful gases. To detect fire in garbage bin temperature sensor is placed, if the temperature goes beyond the predefined threshold value or presence of harmful gas is detected, alarm will be raised to alert the nearby people and organization will be notified using telegram. This will help to keep the polluted places clean in a smart and effective way. The organization will be notified by the system automatically, when the garbage bin is filled, which reduces time for manual checking